Safety and Performance Characteristics of Outpatient Medical Thoracoscopy and Indwelling Pleural Catheter Insertion for Evaluation and Diagnosis of Pleural Disease at a Tertiary Center in Canada - Robert Kyskan; Pen Li; Sunita Mulpuru; Carolina Souza; Kayvan Amjadi (Canadian Respiratory Journal)
Background. Many centers performing medical thoracoscopy (MT) to diagnose pleural disease will insert a chest tube and admit patients to hospital after the procedure, which is inconvenient for patients and contributes to healthcare costs. We report the data on the safety, outcomes, and performance characteristics of outpatient MT with indwelling pleural catheter (IPC) insertion in a large Canadian cohort. Methods. This retrospective cohort study reviewed patients who underwent outpatient MT and IPC insertion under conscious sedation. Patients without complications were discharged the same day. We report the data on safety, outcomes, and performance characteristics of our program. Results. Outpatient MT and IPC insertion was performed on 218 patients. 99.1% of patients were safely discharged the same day. There was no procedure associated mortality. Pleural malignancy (59.6%) and nonspecific pleuritis (29.4%) were the most common pathologies. Pleural nodularity detected endoscopically was excellent at predicting malignancy with a positive predictive value of 92.5% and is more frequently detected endoscopically when compared to CT scan (p<0.001). Conclusions. In the setting of a comprehensive pleural disease program, outpatient MT can be safely performed and is an alternative to an inpatient surgical approach for undiagnosed pleural effusions.